Accuracy of recording and reporting of malaria rapid diagnostic tests in Nigeria - Atobatele, Sunday; Sampson, Sidney; Orya, Evelyn; Okoro, Onyebuchi; Akpiroroh, Ese; Okagbue, Hilary; Gab-deedam, Shiva D.; Bademosi, Olufisayo; Atu, Ginini; Lindblade, Kim A.; Mukhtar, Al-Mustapha; Ayodeji, Oluwafisayo; et al. (Malaria journal, 2025)
Background Malaria remains a major health concern in Nigeria. Rapid diagnostic tests (RDTs) are widely used in health facilities to confirm malaria before treatment. However, concerns remain about healthcare workers (HCWs) adherence to, and reporting of test results. This study assessed the accuracy of RDT results recorded in health facility registers in two states of Nigeria by comparing them with an unbiased reference standard and explored factors influencing interrater agreement. Methods A mixed-method evaluation was conducted in 16 health facilities across Oyo and Sokoto States. RDTs performed by HCWs were photographed using a digital RDT reader and independently re-interpreted by a trained, independent, objective panel. Surveys of health facilities and HCWs collected data on factors that could influence RDT recording. Interrater agreement between RDT results recorded by HCWs in facility registers and the external panel was assessed using Cohen’s kappa. A meta-analytical approach was used to calculate a pooled summary kappa value across facilities, and potential moderators of agreement were examined, including characteristics of facilities, HCWs and RDTs. Results Out of 19,586 RDTs captured, 18,319 were included in the analysis. Overall, 6.2% of RDTs were misrecorded as positive and 3.7% as negative in health facility registers, yielding a positive predictive value of 87.2% (95% confidence interval [CI] 86.4%, 87.8%) and negative predictive value of 92.9%. The overall percentage agreement was 90.2% (95% CI 89.7%, 90.6%), and the pooled kappa statistic was 0.80 (95% CI 0.75, 0.85), indicating strong agreement. However, kappa values varied substantially across facilities (range: 0.59, 0.92). Lower agreement was observed in facilities in Sokoto State and in areas with lower malaria prevalence and test positivity. Faint test lines, found in 8.8% of RDTs, were associated with a significantly increased likelihood of results misrecorded as negative. HCWs were more likely to misrecord RDT results as positive when a malaria diagnosis or antimalarial prescription had been made. Conclusion While overall agreement between facility registers and panel-interpreted RDT results was strong, the proportion of results misrecorded as positive and negative highlight the need for improved training, supportive supervision, and mechanisms to promote accurate RDT interpretation and recording. Targeted interventions are essential to ensure the reliability of routine malaria data and support national control efforts.